A Background to Rural Education Schooling in Australia - Andrew H. Higgins (Journal of Research in Rural Education, 1994)
I introduce a brief history of rural education in Australia byfirst providing ageographical description ofthecountryand thenbydiscussing thedevelopment ofeducation in remote areas. I then consider thehistory ofrural education in onestate, Queensland, as an illustration of developments elsewhere in the country. I conclude by considering the impact the Commonwealth government had on Australian rural education since the1960s.